Utilização da borracha natural no desenvolvimento de elastômeros termoplásticos - Rojas, Galia Johanna Alzate (Universidade Federal de São Carlos, 2010)
Dynamic vulcanization is a process of vulcanization of an elastomer during melt mixing with a thermoplastic. This process results in an elastomeric alloy material with the properties of a conventional thermoset rubber, but which can be processed as a conventional thermoplastic. In this study, thermoplastic elastomers (TPEs) based on natural rubber (NR)/polyprolylene (PP) with various blend ratios were prepared. The TPEs was obtained by dynamic vulcanization of NR/PP using a sulphur (S)/N-tert-butyl-2- benzothiazolesulphenamide (TBBS) and tetramethylthiuram disulphide (TMTD) curative system during processing in the melt state. The crosslinking formation during the processing was confirmed by the increase in the degree of cure of the systems measured by DSC. The dynamic vulcanization process increases the stiffness of the NR phase in the TPEs and modifies the thermal and mechanical behavior. NR/PP TPEs with high content of NR showed superior mechanical performance compared to the uncrosslinked NR/PP blends in terms of tensile strength and Young s modulus. It was obtained an increase in Young s modulus values of NR70/PP30 TPE of 316% than compared to NR70/PP30 conventional blend. The main reason for the high performance was the increase of degree of cure during the reactive processing that became the NR phase more rigid and contributed to the increase in the mechanical resistance of TPEs.
Use of natural rubber in the development of thermoplastics elastomers
Keywords: Blendas poliméricas; Elastômero; Borracha; Vulcanização dinâmica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA